2011
DOI: 10.1177/1043454210397755
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Scale to Measure Parental Worry and Their Attitudes Toward Childhood Cancer After Successful Completion of Treatment

Abstract: The purpose of this study is to develop and evaluate the psychometric characteristics of a scale designed to measure parents' attitude toward childhood cancer after treatment has ended. In this study, the 2 theoretical frameworks (theory of attitude and theory of worry) were used as they related to the study. An attitude is an idea charged with negative or positive emotion, directed to a psychological object, such as cancer. A sample of 84 White, middle class, American parents (n = 49 mothers, n = 35 fathers) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
1
12
0
2
Order By: Relevance
“…We found that impaired parent emotional functioning was strongly associated with worse parent outlook, consistent with previous observations [16,19,4552]. Such emotional stress and poor adjustment has negative consequences for the parent [48,53] and in turn, the child [5457].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that impaired parent emotional functioning was strongly associated with worse parent outlook, consistent with previous observations [16,19,4552]. Such emotional stress and poor adjustment has negative consequences for the parent [48,53] and in turn, the child [5457].…”
Section: Discussionsupporting
confidence: 91%
“…The multicenter design and the relatively diverse sample (30% Hispanic or nonwhite), particularly in light of the study population [44,61,62], are other strengths of this study. Finally, this study builds on previous studies that have described parent fear, stress, or impaired psychological functioning during or after HSCT [16,19,4552], and illustrates specific parental thoughts and thought patterns before their child’s transplantation, deepening our understanding of their lived experience.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Assessment of potentially vulnerable parents may involve collaboration with mental health members of the professional team to identify parents that may be at risk for issues with adaptation and coping posttreatment and proactively provide support and psychoeducation. For example, Duran (2011) piloted the Parental Worry and Attitudes Toward Childhood Cancer scale to measure parents’ concerns about recurrence of their child’s cancer with the ultimate goal of intervention development for parents in need. Proactive strategies to avert distress may include staff discussions with parents about what to expect emotionally after active treatment ends and psychoeducation sessions to support parents in their transition.…”
Section: Discussionmentioning
confidence: 99%
“…(43) These studies can be divided according to the type of risk investigated. There are risks where the parent has a certain margin of control (44) -food allergies, for example, (25) Internet use, (45) or sexually transmitted diseases (46) -and then there are risks that in many ways are beyond parents' direct control (and are therefore comparable with climate change) such as disease, (47)(48)(49) children with special needs, (50,51) food and eating, (21) school, (52) and the environment. (53,54) It is worries of the latter sort-uncontrollable, confusing, and worrying because of their huge consequences for future generations-that have been as good as ignored in the literature.…”
Section: Previous Researchmentioning
confidence: 99%